Exhaust Measurement and Emission Control—Biodiesel Involvement in Diesel Engine. (1st January 2016) - Kanthavelkumaran, N.; Seenikannan, P.; Kumaresh, E.
Abstract : This research focusing the performance and emission characteristics study on the application of biofuel emulsions as alternate fuel used Kirloskar AV1 Direct Injection Diesel engine. Diesel engine performance was compared using different fuels, namely Diesel, Jatropha Methyl Ester and Jatropha Methyl Ester Wood Pyrolysis Oil emulsion, by applying various loads. Emission characteristics were observed and measured by using MRU Exhaust gas analyzer, Optrons 1600 smoke meter. From this experimentation result shows that the biofuel emulsions improved better combustion efficiency with diesel engine performance. It is found that oxides of nitrogen emission of JE15 and smoke darkness of Y2JE10 was reduced 3% and 3.7%, when compared to diesel and other blends respectively. After evaluating the results, these kinds of biofuels are concentrated more and more environment support and safety.